Penggunaan Model Pembelajaran Numbered Heads Together pada Pelajaran IPA Materi Pesawat Sederhana untuk Meningkatkan Hasil dan Motivasi Belajar Siswa Kelas VIII.1 MTs N 1 Siak - Yenti, Nelvi (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2022)
This study aims to test the Numbered Heads Together (NHT) learning model in increasing the motivation and learning outcomes of students on simple aircraft science material based on the Classroom Action Research (PTK) method. The research was conducted in August - September 2021 to class VIII.1 MTs N 1 Siak students totaling 34 people. Data collection techniques include observation instruments, interviews, questionnaires, documentation, tests, and worksheets. Data analysis was carried out through a description of the research results with a qualitative approach. Indicators of research success are seen from the learning outcomes of 34 students who can meet the scores above the KKM standard (< 76) as much as 85% of the total number of students. The results of the study concluded that the use of the NHT learning model on simple aircraft science material in class VIII.1 MTs N 1 Siak for the 2021/2022 academic year is said to have met the research success indicator, where students who successfully meet the KKM score standard <76 reach more than 85%. Thus the NHT model can be used as an appropriate alternative to carry out active science learning activities in order to optimize learning outcomes and increase student learning motivation